A new fluorescence turn-on chemosensor for nanomolar detection of Al3+ constructed from a pyridine–pyrazole system. (29th January 2018) - Naskar, Barnali; Das, Kinsuk; Mondal, Ramij R.; Maiti, Dilip K.; Requena, Alberto; Cerón-Carrasco, José Pedro; Prodhan, Chandraday; Chaudhuri, Keya; Goswami, Sanchita
Abstract : A pyridine–pyrazole based fluorescence turn-on chemosensor provides access to selective detection of Al 3+ in solution as well as in HepG2 living cells. Abstract : Herein, a new probe, 5-methyl-1-pyridin-2-yl-1 H -pyrazole-3-carboxylic acid (1-pyridin-2-yl-ethylidene)-hydrazide (Hmppc ), bearing a pyridine–pyrazole moiety, was synthesized, which offered potential for chemical sensing of Al 3+ . Investigations of the fluorescence behaviour ofHmppc in DMSO/H2 O (2 : 8, v/v) solution under biologically relevant conditions in HEPES buffer (pH = 7.4) displayed a dramatic switch-on response to Al 3+ as a result of chelation-induced enhanced fluorescence (CHEF). Detailed experimental studies reveal thatHmppc can detect Al 3+ in solution with high sensitivity and selectivity, having a detection limit of 1.2 nM. Furthermore, to demonstrate the analytical potential ofHmppc, we validated our sensing system as a naked eye detector for Al 3+ . Interestingly, bioimaging studies on HepG2 cells demonstrated thatHmppc responded selectively towards Al 3+, allowing real time detection of Al 3+ in living cells.